Phototoxicity inhibition effect of vitamin c and glutathione against several photosensitizers - Rosmelia, Rosmelia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Ultraviolet B radiation on the skin, in the presence of photosensitizers such as quinolones, sulfacetamide, and non-steroid antiinflammatory.could induce phototoxicity due to cell membrane photo-oxidation. Antioxidants, such as vitamin C and glutathione, have been reported capable to neutralize free radicals and prevent oxidative reactions. Scientific report about the role of such antioxidants in the prevention of phototoxicity due to photosensitizers on above, is still limited.Objectives: To compare phototoxicity inhibition effect between vitamin C and glutathione and phototoxicity potency of several photosensitizersMaterials and Methods: A simple experimental design is used to compare phototoxicity potency of 0.08 mg/ml ofloxacin, 0.004 mg/ml furosemide, and 0.02 mg/ml ketoprofen, and effects of 0.2 mg/ml vitamin C, and 0.12 mg/ml glutathione on phototoxicity reactions of erythrocytes exposed to 1.6 J/cm2 UVB. Phototoxicity reaction was measured by hemoglobin released by targeted erythrocytes using spectrophotometer.Results: Hemoglobin released by photosensitizers were ofloxacin 6.760ÃÂ±.1.669, furosemide 6.532ÃÂ±1.271, ketoprofen 6.710 ÃÂ±1.826 g/dI respectively. There was no significant difference of haennoglobine released among them (p>0.051. Addition of vitamin C could reduce phototoxicity of photosensitizer very significantly (p